In mixed company : communicating in small groups and teams - Rothwell, J. Dan (Wadsworth, Cengage Learning, 2013)
The market leader for the small group communication course, Rothwell's In Mixed Company uses a narrative approach to help you comprehend both theory and application-an approach that enables you to apply small group communication concepts not only in class but in your life